(untitled) (Journal of Economic Additions, 2025)
Public financial governance is essential for ensuring transparency, efficiency, and accountability in the management of public funds. This study aims to explore international experiences in implementing public financial governance reforms, highlighting successful models from the United Kingdom, Sweden, South Korea, and the United States. It examines fiscal responsibility laws, digital financial management systems, and performance-based budgeting approaches that have strengthened governance in these countries. The study concludes by emphasizing the need to activate governance mechanisms to enhance independent oversight, digitalization, and structured budgeting frameworks.. Jel Classification Codes: H11,H61,H87